Perbandingan Hasil Belajar Kognitif Peserta Didik Melalui Pembelajaran Guided Discovery dan Guided Inquiry pada Materi Kesetimbangan Kimia - Winda Fajriati; Zonalia Fitriza (Universitas Negeri Padang, 2020)
The purpose of this research is to compare the student’s result study who learn using Guided Discovery models and Guided Inquiry models. The research sample is 2 classes XI Science in one of the high schools at SMAN 9 Padang, sample class 1 is the Guided Discovery model treatment and sample class 2 is with the Guided Inquiry model. The research design was Randomized Posttest-Only Comparison Controls Groups Design. The instrument in the study was the learning achievement test (posttest). The results of the study stated that: (1) learning outcomes with the Guided Discovery and Guided Inquiry models there were differences, but not significant. Evidenced by the averages student’s result study of the two classes that have a slight difference, namely sample class 1 (81.86) while sample class 2 (84.36). (2) The results of the statistical test of hypothesis testing with the t test (α = 0.05) obtained tcount = 0.65 and ttable = 1.99. The results show thats the Guided Discovery and Guided Inquiry models effectively improve student learning outcomes.